Jujube and green tea extracts protect human fibroblast cells against UVB-mediated photo damage and MMP-2 and MMP-9 production - Zahra Abotorabi; Mohsen Khorashadizadeh; Mina Arab; Mohammad Hassanpour Fard; Asghar Zarban (Mashhad University of Medical Sciences, 2020)
Objective: Oxidative stress and ultraviolet B (UVB) irradiation are known as principal inducers of DNA damage and modulators of gene expression in aging process and skin photoaging, which are associated with upregulation of matrix metalloproteinases (MMPs). Because of the antioxidant capacity of jujube and green tea, we decided to determine their protective effects of human fibroblast cells against UVB-induced photo-damage and reduction of MMP-2 and MMP-9 expression. Materials and Methods: We exposed human fibroblast cells to different doses of UVB (0-20mJ/cm2) with or without different concentrations of jujube and green tea extracts. Cell viability was assessed using MTT assay. Total antioxidant capacity and free radical scavenging activity of cell supernatant were assessed using FRAP and DPPH methods, respectively. The concentrations of MMP-2 and MMP-9 in the samples were determined by ELISA kits. Results: Fibroblast cells viability, 24 hr after UVB irradiation, reduced about 70% compared to the controls. Pre-treatment of the cells with jujube extract (8mg/ml) increased the cell viability by almost 85% while green tea (0.5mg/ml) protected the irradiated cells by 71%. Also, MMP-2 and MMP-9 content decreased in a concentration-dependent manner in the cells pre-treated with jujube and green tea extracts. Conclusion: These data suggest that jujube and green tea could be useful to attenuate solar UVB light-induced oxidative stress and skin photoaging and can be suggested as a potential candidate for the development of new anti-UVB medicines and cosmetic products.